2004
DOI: 10.1037/0278-7393.30.4.739
|View full text |Cite
|
Sign up to set email alerts
|

Verbalizing Facial Memory: Criterion Effects in Verbal Overshadowing.

Abstract: This article investigated the role of the recognition criterion in the verbal overshadowing effect (VOE). In 3 experiments, people witnessed an event, verbally described a perpetrator, and then attempted identification. The authors found in Experiment 1, which included a "not present" response option and both perpetrator-present (PP) and perpetrator-absent (PA) lineups, an increased reluctance to identify a person from both lineup types after verbalization. Experiment 2 incorporated a forced-choice procedure, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
94
1
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(104 citation statements)
references
References 43 publications
6
94
1
3
Order By: Relevance
“…An alternative would be to use any nonconflicting detail mentioned in the descriptions (i.e., a comprehensive description). It is often difficult to determine how descriptions are combined when researchers fail to report how descriptions are obtained or produced (e.g., Clare & Lewandowsky, 2004 provided no LINEUP FAIRNESS MEASURES 7 information; Haw &Fisher, 2004 andRyan, 1993 indicated they constructed a general description). Thus, we examined whether lineup fairness measures vary based on the type of description presented to mock witnesses.…”
Section: Descriptionmentioning
confidence: 99%
“…An alternative would be to use any nonconflicting detail mentioned in the descriptions (i.e., a comprehensive description). It is often difficult to determine how descriptions are combined when researchers fail to report how descriptions are obtained or produced (e.g., Clare & Lewandowsky, 2004 provided no LINEUP FAIRNESS MEASURES 7 information; Haw &Fisher, 2004 andRyan, 1993 indicated they constructed a general description). Thus, we examined whether lineup fairness measures vary based on the type of description presented to mock witnesses.…”
Section: Descriptionmentioning
confidence: 99%
“…On the other hand, simple accounts often fall short when models are fit to data. There has been some progress in terms of fitting decision models to data (Clare & Lewandowsky, 2004;Clark, 2003), but this work has just scratched the surface.…”
Section: Didn't Do It Then Why Did the Witness Identify Him?mentioning
confidence: 99%
“…Clare and Lewandowsky (2004) showed that participants who had previously described the target face, compared to those providing no description, were more likely to say that the target was "not present" in a recognition line-up (i.e. they adopted a more conservative response bias).…”
Section: Comparing Effects Of Verbalization In Imagery and Face Recogmentioning
confidence: 99%
“…a retrieval-based interference account, e.g. Brandimonte & Collina, 2008, Schooler & Engstler-Schooler, 1990 or response bias criterions (Clare & Lewandowsky, 2004). Due to the nature of the recognition memory tests we used, a shift in response criterion account cannot apply: participants were forced to identify the target form from the recognition test, and this removed the opportunity to observe changes in response bias (c.f.…”
Section: Processing Vs Representational Accountsmentioning
confidence: 99%
See 1 more Smart Citation